CHD7 and 53BP1 regulate distinct pathways for the re-ligation of DNA double-strand breaks - Rother, Magdalena B.; Pellegrino, Stefania; Smith, Rebecca; Gatti, Marco; Meisenberg, Cornelia; Wiegant, Wouter W.; Luijsterburg, Martijn S.; Imhof, Ralph; Downs, Jessica A.; Vertegaal, Alfred C. O.; Huet, Sébastien; Altmeyer, Matthias; et al. (Nature communications, 2020)
Chromatin structure is dynamically reorganized at multiple levels in response to DNA double-strand breaks (DSBs). Yet, how the different steps of chromatin reorganization are coordinated in space and time to differentially regulate DNA repair pathways is insufficiently understood. Here, we identify the Chromodomain Helicase DNA Binding Protein 7 (CHD7), which is frequently mutated in CHARGE syndrome, as an integral component of the non-homologous end-joining (NHEJ) DSB repair pathway. Upon recruitment via PARP1-triggered chromatin remodeling, CHD7 stimulates further chromatin relaxation around DNA break sites and brings in HDAC1/2 for localized chromatin de-acetylation. This counteracts the CHD7-induced chromatin expansion, thereby ensuring temporally and spatially controlled ‘chromatin breathing’ upon DNA damage, which we demonstrate fosters efficient and accurate DSB repair by controlling Ku and LIG4/XRCC4 activities. Loss of CHD7-HDAC1/2-dependent cNHEJ reinforces 53BP1 assembly at the damaged chromatin and shifts DSB repair to mutagenic NHEJ, revealing a backup function of 53BP1 when cNHEJ fails. Chromatin is dynamically remodeled in response to DNA damage in favour of repair. Here the authors reveal how the chromatin remodeler CHD7 and chromatin binding protein 53BP1 regulate distinct DNA repair pathways.